2016
DOI: 10.1159/000448914
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sickle Cell Trait and Reliability of Self-Reported Status among Expectant Parents in Nigeria: Implications for Targeted Newborn Screening

Abstract: Background/Aims: Sickle cell disease (SCD) is a life-threatening, autosomal recessive blood disorder prevalent in sub-Saharan Africa. We identified the prevalence of sickle cell trait (SCT) among pregnant women and their male partners in Enugu State, Nigeria, and determined the accuracy of self-reported sickle cell status and its reliability for identifying high-risk newborns for targeted screening. Methods: We conducted a nested cohort study of expectant parents enrolled in the Healthy Beginning Initiative (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 27 publications
2
27
0
3
Order By: Relevance
“…The 2016 global EM articles selected for full review are listed in Table 4. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Nineteen articles were selected for inclusion, of which 15 (79%) were categorized as emergency care, three (16%) were categorized as development, and one (5%) was categorized as disaster response articles. Eighteen (95%) articles were original research manuscripts and one (5%) was a review article.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2016 global EM articles selected for full review are listed in Table 4. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Nineteen articles were selected for inclusion, of which 15 (79%) were categorized as emergency care, three (16%) were categorized as development, and one (5%) was categorized as disaster response articles. Eighteen (95%) articles were original research manuscripts and one (5%) was a review article.…”
Section: Resultsmentioning
confidence: 99%
“…The use of the Emergency Triage Assessment and Treatment (ETAT) tool for pediatric patients continues to spread, with Kapoor et al 33 demonstrating the dissemination of ETAT from the referral hospitals down to the primary health center level in Guatemala. In Nigeria, Burnham-Marusich et al 18 used a nested design to conduct two-step screening for sickle cell disease, which due to pain crises and acute infections poses a heavy burden on the emergency care system in sub-Saharan Africa. In another article studying anemia, Sawe et al 26 demonstrated that clinical gestalt was a fair alternative to laboratory testing in diagnosing anemia in resource-limited settings.…”
Section: Plos Onementioning
confidence: 99%
“…It can be used to increase access to health information and reduce turnaround times for receipt of laboratory test results by skilled birth attendants. Studies of mHealth apps to improve maternal health in low-income countries have focused primarily on using mobile phones for data collection, appointment reminders, health promotion and education, and provider-to-provider or person-to-person communication [ 12 , 13 ]. Specifically in Nigeria, mHealth has been used by community health workers for decision support (prenatal care decision support algorithm), health education, and data collection, as well as by clients for appointment reminders [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our rationale for focusing on HIV, HBV, and SCD for mHealth is based on several factors: (1) we found high prevalences of HIV, hepatitis B surface antigen, and sickle cell trait of 2% [ 10 ], 5%, and 22% [ 13 ], respectively, in pregnant women in the communities where HBI was implemented; (2) an integrated approach to screen for multiple diseases rather than a single condition was widely acceptable by the community; and (3) the integration of both infectious and chronic diseases highlights the double burden facing sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…A prevalência da heterozigose para HbS é maior nos países africanos, e, na Nigéria, atinge aproximadamente 20% 10 . Em afro-americanos e na Jamaica este número chega a 10% 9 .…”
Section: Introdução|unclassified